PENGARUH KODE ETIK AKUNTAN PUBLIK TERHADAP KUALITAS HASIL AUDIT PADA KANTOR AKUNTAN PUBLIK DI BANDUNG - Juhara, Djajun (Majalah Bisnis & IPTEK, 2021)
The purpose of this study was to examine the effect of Kode Etik Akuntan Publik for the quality of audits. The population in this study is the auditors of five KAP in the city of Bandung. Determination of sample, using a simple random sampling method. The data in this research is obtained by distributing questionnaires to the respondents on Akuntan Publik in the city of Bandung. These result prove that Kode Etik Akuntan Publik effect on audit quality. So the higher Kode Etik Akuntan Publik are owned by auditor it will improve the quality of audits. Keywords: ethic code, audit quality.